2019
DOI: 10.1039/c9py01363f
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable sulfone-containing polymersviaring-opening polymerization of macroheterocyclic siloxane monomers: synthesis, properties and recyclability

Abstract: The first recyclable sulfone-containing polysiloxanes were synthesized via an anionic ring-opening polymerization of macroheterocyclic siloxane monomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The TGA data presented in Figure 5 indicates that following incorporation of BSM, all benzylsulfonyl polysiloxanes exhibited higher T d and T max than the neat PDMS (Table S1, run 6). For instance, in the case of PSMS 18 , an obvious increase in T d and T max from 269°C (PDMS) to 320°C (PSMS 18 ) and from 309°C to 379°C was observed, respectively (Figure 5a). The increase was attributed to the incorporation of aromatic and sulfone segments.…”
Section: Thermal Properties Of the Copolymersmentioning
confidence: 94%
See 3 more Smart Citations
“…The TGA data presented in Figure 5 indicates that following incorporation of BSM, all benzylsulfonyl polysiloxanes exhibited higher T d and T max than the neat PDMS (Table S1, run 6). For instance, in the case of PSMS 18 , an obvious increase in T d and T max from 269°C (PDMS) to 320°C (PSMS 18 ) and from 309°C to 379°C was observed, respectively (Figure 5a). The increase was attributed to the incorporation of aromatic and sulfone segments.…”
Section: Thermal Properties Of the Copolymersmentioning
confidence: 94%
“…Previous studies suggested KOH as the suitable catalyst for homopolymerization of BSM in dimethyl sulfoxide (DMSO). [18] Accordingly, the copolymerization of BSM with octamethylcyclosiloxane (D 4…”
Section: Copolymerization Of Bsm With Cyclosiloxanementioning
confidence: 99%
See 2 more Smart Citations
“…Sulfone-containing silicone copolymers were synthesized by ring-opening copolymerization of octamethylcyclosiloxane (D 4 ), 2,4,6,8-tetravinyl-2,4,6,8-tetramethylcyclotetrasiloxane (D 4 Vi ), and benzylsulfonyl macroheterocyclosiloxane (BSM) (Scheme 1a). [12] The copolymerization was conducted in a mixed solvent of dimethylformamide (DMF) and toluene at 120 °C using KOH as the catalyst. As shown in Figure S1, Supporting Information, the ring-opening polymerization was monitored by the analysis of the 1 H NMR spectrum, which showed a downfield shift of two proton peaks at 2.52 ppm (SO 2 CH 2 CH 2 ) and 0.74 ppm (CH 2 CH 2 Si) to 3.00 and 1.09 ppm, respectively.…”
Section: The Preparation Of a Series Of Luminescent Perovskite-silicomentioning
confidence: 99%